2008
DOI: 10.2174/157015908783769662
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Related Changes in Regulation of NMDA Receptor Functions

Abstract: Long-term alcohol exposure may lead to development of alcohol dependence in consequence of altered neurotransmitter functions. Accumulating evidence suggests that the N-methyl-D-aspartate (NMDA) type of glutamate receptors is a particularly important site of ethanol's action. Several studies showed that ethanol potently inhibits NMDA receptors (NMDARs) and prolonged ethanol exposition leads to a compensatory "up-regulation" of NMDAR mediated functions. Therefore, alterations in NMDAR function are supposed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 194 publications
(221 reference statements)
4
106
0
1
Order By: Relevance
“…Therefore our first hypothesis "there would be no significant difference found between the mean scores of mental health of adolescent and adult drug addicts" is rejected. Our findings bear some similarities with those of previous studies like Khushehmehri et al [7] and Nagy [8]. While taking about the second independent variable i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore our first hypothesis "there would be no significant difference found between the mean scores of mental health of adolescent and adult drug addicts" is rejected. Our findings bear some similarities with those of previous studies like Khushehmehri et al [7] and Nagy [8]. While taking about the second independent variable i.e.…”
Section: Discussionsupporting
confidence: 92%
“…They also found that the young are more disposed to drugs. Nagy [8] in his study discovered that adolescents have indicated differential react to episodic drinking. Results revealed that alcohol consumption significantly damaged the brain of both the adults and the adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this is evidenced by increased liver injury upon loss of the NMDA signaling pathway and the hepatoprotection provided with aspartate supplementation. Furthermore, ethanol has been proposed to be a noncompetitive antagonist of the NMDA receptor in neurons (9,18). If the same effect is present in Kupffer cells, it will result in loss of NMDA-induced downregulation of inflammasome activity and may provide another mechanism of the hepatic immune dysregulation induced by ethanol.…”
Section: G735mentioning
confidence: 99%
“…(NMDA) receptors serve as calcium channels, which play critical roles in neuronal functions (Nagy, 2008;Kalia et al, 2008). An NMDA receptor (NR) 1 subunit forms a complex with each member of NR2 subfamily, and the complex functions as an NMDA receptor (Nagy, 2008;Kalia et al, 2008).…”
Section: It Is Common Knowledge That N-methyl-d-aspartatementioning
confidence: 99%
“…An NMDA receptor (NR) 1 subunit forms a complex with each member of NR2 subfamily, and the complex functions as an NMDA receptor (Nagy, 2008;Kalia et al, 2008). More recently, we found superinduced expression of the Grin2c gene encoding the NR2C subunit, a member of the NR2 subfamily, during the development of liver enlargement with hepatocellular hypertrophy in rats treated with phenobarbital (PB), chlofibrate (CF), or piperonyl butoxide (PBO) (Nemoto et al, 2011a).…”
Section: It Is Common Knowledge That N-methyl-d-aspartatementioning
confidence: 99%